Meningkatkan Hasil Belajar Fisika Melalui Penerapan Model Pembelajaran Contextual Teaching and Learning (CTL) di SMA N Sukamenang - Sapira Meliani; Wahyu Arini; Ovilia Putri Utami Gumay (Prosiding Silampari Conference of Life Sciences and Techonology (Silamparilist), 2026)
This study aims to determine the improvement in physics learning outcomes among Grade X students at SMA Negeri Sukamenang following the implementation of the Contextual Teaching and Learning (CTL) model. The study employed a quantitative approach using an experimental method. The sample consisted of 34 students from class X.2 at SMA Negeri Sukamenang, selected via simple random sampling. Data were collected using a 15-item multiple-choice learning achievement test administered as both a pre-test and a post-test. The obtained data were analyzed using a t-test at a significance level of 0.05 to test the research hypothesis. The results indicate that the students' average learning outcome score increased from 69.76 in the pre-test to 81.74 in the post-test, with a learning mastery rate of 88.24%. Hypothesis testing results showed that the calculated t-value exceeded the t-table value; thus, the null hypothesis (H₀) was rejected and the alternative hypothesis (Hₐ) was accepted. Consequently, the implementation of the Contextual Teaching and Learning (CTL) model is proven to have a significant effect on improving the physics learning outcomes of Grade X students at SMA Negeri Sukamenang.